Cumulative antitumor effect of bismuth lipophilic nanoparticles and cetylpyridinium chloride in inhibiting the growth of lung cancer - García Cuellar, Claudia María; Hernández Delgadillo, René; Torres Betancourt, Jesús Alejandro; Solís Soto, Juan Manuel; Meester, Irene; Sánchez Pérez, Yesennia; Pineda Aguilar, Nayely; Nakagoshi Cepeda, Sergio Eduardo; Sánchez Nájera, Rosa Isela; Nakagoshi Cepeda, María Argelia Akemi; Chellam, Shankararaman; Cabral Romero, Claudio (Sage Publishing, 2023)
Objective: To determine the combined antitumor effect of bismuth lipophilic nanoparticles (BisBAL NP) and cetylpyridinium chloride (CPC) on human lung tumor cells. Material and methods: The human lung tumor cells A549 were exposed to 1–100 µM BisBAL NP or CPC, either separately or in a 1:1 combination. Cell viability was measured with the PrestoBlue assay, the LIVE/DEAD assay, and fluorescence microscopy. The integrity and morphology of cellular microtubules were analyzed by immunofluorescence. Results: A 24-h exposure to 1 µM solutions reduced A549 growth with 21.5% for BisBAL NP, 70.5% for CPC, and 92.4% for the combination ( p < 0.0001), while a 50 µM BisBAL NP/CPC mixture inhibited cell growth with 99% ( p < 0.0001). BisBAL NP-curcumin conjugates were internalized within 30 min of exposure and could be traced within the nucleus of tumor cells within 2 h. BisBAL NP, but not CPC, interfered with microtubule organization, thus interrupting cell replication, similar to the action mechanism of docetaxel. Conclusion: The growth inhibition of A549 human tumor cells by BisBAL NP and CPC was cumulative as of 1 µM. The BisBAL NP/CPC combination may constitute an innovative and cost-effective alternative for treating human lung cancer.